2008
DOI: 10.1351/pac200880040791
|View full text |Cite
|
Sign up to set email alerts
|

Use of sultines in the asymmetric synthesis of polypropionate antibiotics

Abstract: At low temperature and in the presence of an acid catalyst, SO 2 adds to 1,3-dienes equilibrating with the corresponding 3,6-dihydro-1,2-oxathiin-2-oxides (sultines). These compounds are unstable above -60°C and equilibrate with the more stable 2,5-dihydrothiophene 1,1-dioxides (sulfolenes). The hetero-Diels-Alder additions of SO 2 are suprafacial and follow the Alder endo rule. The sultines derived from 1-oxy-substituted and 1,3-dioxydisubstituted 1,3-dienes cannot be observed at -100°C but are believed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 301 publications
1
12
0
1
Order By: Relevance
“…[c] The opposite enantiomer than the one shown was obtained. [d] This result has been previously published, see Vogel et al [7] Scheme 4. Possible reaction pathways for a SO 2 -induced one-pot, two-directional oxyallylation cascade.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…[c] The opposite enantiomer than the one shown was obtained. [d] This result has been previously published, see Vogel et al [7] Scheme 4. Possible reaction pathways for a SO 2 -induced one-pot, two-directional oxyallylation cascade.…”
Section: Resultssupporting
confidence: 79%
“…[4] We have reported the one-pot synthesis of stereotriads 7 using an oxyallylation reaction cascade that combines electron-rich dienes 1 and carbon nucleophiles 4, such as enoxysilanes, through SO 2 -umpolung (Scheme 1). [5,6,7] Dienes 1, containing a 1-arylethyl chiral auxiliary, [8] undergo heteroDiels-Alder (HDA) addition with SO 2 to generate six-membered sultine 2, which is subsequently broken down to the zwitterionic species 3 by Lewis acid assisted heterolysis. NuAbstract: Herein, a major breakthrough in a sulfur dioxide-mediated oxyallylation cascade reaction is reported that allows the preparation of complex long-chain polyketide fragments with more than ten stereogenic centers through a carefully designed desymmetrization process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] We have reported one-pot syntheses of the stereotriads 7 through oxyallylation reaction cascades in which the electron-rich dienes 1 and the enoxysilanes 4 are coupled through SO 2 umpolung (Scheme 1). [6][7][8] The dienes 1, each containing a 1-arylethyl chiral auxiliary, [9] undergo hetero-(Z)-enol isobutyrate units remained intact were obtained. After suitable protection, these were converted into their corresponding lithium (Z)-enolates, which could react with isopropylidene D-glyceraldehyde [(+)-9] to give aldol products that were reduced to various stereodecads (polyketides with ten contiguous stereogenic centres).…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] As these compounds can also be obtained by the H-ene reaction of alkenes with SO 2 /BCl 3 , followed by neutralization with NH 3 and reaction with silyl chlorides [10] (Scheme 5), we wondered whether these systems could be employed as nucleophilic allylating agents.…”
Section: A C H T U N G T R E N N U N G [Pdcl 2 a C H T U N G T R E N mentioning
confidence: 99%